2023
DOI: 10.1111/adb.13317
|View full text |Cite
|
Sign up to set email alerts
|

Delta‐9‐tetrahydrocannabinol modulates pain sensitivity among persons receiving opioid agonist therapy for opioid use disorder: A within‐subject, randomized, placebo‐controlled laboratory study

Joao P. De Aquino,
Julia Meyerovich,
Catherine Z. Xie
et al.

Abstract: The opioid and cannabinoid receptor systems are inextricably linked—overlapping at the anatomical, functional and behavioural levels. Preclinical studies have reported that cannabinoid and opioid agonists produce synergistic antinociceptive effects. Still, there are no experimental data on the effects of cannabinoid agonists among humans who receive opioid agonist therapies for opioid use disorder (OUD). We conducted an experimental study to investigate the acute effects of the delta‐9‐tetrahydrocannabinol (TH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…The authors of this latter study also attempted to test 40 mg of dronabinol, but found that this dosage induced sinus tachycardia, anxiety and panic resulting in discontinuation. Interestingly, further research has suggested a potential biphasic effect of THC, with lower doses producing anxiolysis and analgesia and conversely, higher doses able to increase pain sensitivity and anxiety [ 62 ]. De Aquino et al investigated the effect of varying doses of dronabinol (10 mg and 20 mg) on pain sensitivity among participants receiving methadone therapy for OUD and found that while both doses lead to lower total pain scores than placebo, 10 mg was more effective than 20 mg in this regard [ 62 ].…”
Section: Medicinal Cannabis As An Emerging Therapy For Opioid Use Dis...mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of this latter study also attempted to test 40 mg of dronabinol, but found that this dosage induced sinus tachycardia, anxiety and panic resulting in discontinuation. Interestingly, further research has suggested a potential biphasic effect of THC, with lower doses producing anxiolysis and analgesia and conversely, higher doses able to increase pain sensitivity and anxiety [ 62 ]. De Aquino et al investigated the effect of varying doses of dronabinol (10 mg and 20 mg) on pain sensitivity among participants receiving methadone therapy for OUD and found that while both doses lead to lower total pain scores than placebo, 10 mg was more effective than 20 mg in this regard [ 62 ].…”
Section: Medicinal Cannabis As An Emerging Therapy For Opioid Use Dis...mentioning
confidence: 99%
“…Interestingly, further research has suggested a potential biphasic effect of THC, with lower doses producing anxiolysis and analgesia and conversely, higher doses able to increase pain sensitivity and anxiety [ 62 ]. De Aquino et al investigated the effect of varying doses of dronabinol (10 mg and 20 mg) on pain sensitivity among participants receiving methadone therapy for OUD and found that while both doses lead to lower total pain scores than placebo, 10 mg was more effective than 20 mg in this regard [ 62 ]. It may be that dronabinol has a narrow therapeutic window for mediating withdrawal symptoms without producing troublesome adverse effects.…”
Section: Medicinal Cannabis As An Emerging Therapy For Opioid Use Dis...mentioning
confidence: 99%
“…Patients receiving benzodiazepines or testing positive for substances other than methadone and cannabinoids were excluded. Further details on the inclusion and exclusion criteria are discussed in De Aquino et al 7…”
Section: Participantsmentioning
confidence: 99%
“…Approximately 68% of participants self-identified as White, 6% as African American or Black, and 8% as Hispanic or Latin-American. More details on participant demographics can be found in De Aquino et al 7…”
Section: Participant Demographicsmentioning
confidence: 99%
See 1 more Smart Citation